Reducing the fern genus Dryopsis to Dryopteris and the systematics and nomenclature of Dryopteris subgenus Erythrovariae section Dryopsis (Dryopteridaceae) - Zhang, Li-Bing (Phytotaxa, 2012)
The fern genus Dryopsis (Dryopteridaceae) is characterized by the presence of multicellular hairs and costal and costular grooves closed near their bases. Following a recent molecular analysis the monophyletic Dryopsis is nested in a paraphyletic Dryopteris and therefore should be viewed as part of an expanded Dryopteris. The current paper treats Dryopsis as a section of D. subg. Erythrovariae because both of these two taxa have bullate scales and importantly Dryopsis has been resolved as sister to D. subg. Erythrovariae sect. Erythrovariae. Twenty-two species are here recognized in D. sect. Dryopsis. Included in this treatment are nine new combinations, names and statuses, and five names are lectotypified. The present study further located and cited types of an additional 37 related names, many of which have been poorly to science. A key and distributional information of every species recognized is given and related nomenclatural issues are discussed. The nine new names, combinations and statuses include Dryopteris sect. Dryopsis, D. dulongensis, D. leiboensis, D. nidus, D. nushanensis, D. submariformis, D. wantsingshanica, D. crassirachis and D. × fauriei. The following five names are lectotypified: Ctenitis silaensis, C. tibetica, Dryopteris aureovestita, D. mariformis, and Polystichum transmorrisonensis.